TINGKAT KEPUASAN PETANI TERHADAP PENGGUNAAN HAND TRACTOR - Muharam, Aditya; Hartoyo, Tedi; Darusman, Dedi (Jurnal Agristan, 2024)
Optimizing the use of agricultural technology encourages farmers to increase the use of hand tractor agricultural technology machinery. The increasing use of hand tractors by farmers cannot be used as a definite measure of farmer satisfaction with hand tractors. This study aims to analyze the level of importance of farmers and the level of performance of hand tractor attributes, attributes that need to be prioritized in supporting consumer satisfaction, and the level of farmer satisfaction with the use of hand tractors. The method used in this study is a survey. This research was conducted in Cikajang District, Garut Regency. The sampling technique uses purposive sampling method with a total of 40 respondents who own and use hand tractors. The analytical tools used are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the analysis of hand tractor attributes show that the level of importance is included in the important category and the level of performance is included in the good category. An attribute that is a top priority to improve its performance is to provide a warranty. The satisfaction index is 69.53 percent, which means that farmers are satisfied with the performance of hand tractor attributes.Â